A TEST OF GRAHAM'S AND LYNCH'S STOCK SCREENING CRITERIA ON SHARES TRADED ON THE INDONESIAN STOCK EXCHANGE (IDX) - Dwi Kartikasari (Journal of Indonesian Economy and Business (JIEB), 2016)
Benjamin Graham and Peter Lynch listed criteria for screening stocks, which investors could use to identify undervalued stocks that would outperform the market. Numerous tests have been conducted in the United States and other countries, but not yet in Indonesia. Thus, the author aims to test the applicability of Graham’s and Lynch’s formulation on shares traded on the Indonesian Stock Exchange (IDX) by screening stocks that meet the various sets of Graham's and Lynch's criteria and then measuring the performance of the portfolios over the years from 2010 to 2014. The author uses a simple linear regression to measure the performance of the portfolios against the IDX Composite (IHSG). The author discovered that investors who used the combined criteria of Lynch earned positive risk-adjusted returns, of 28.81 percent per year in 2010-2012 and 27.33 percent per year in 2012-2014. While investors who used a combination of two of Graham’s criteria obtained significant risk-adjusted returns of 47.55 percent annually in 2010-2012 and 5.92 percent annually in 2012-2014. However, investors who implemented a combination of three of Graham’s criteria did not earn positive risk-adjusted returns consistently during the research period. The increasingly complex criteria do not improve the performance of the portfolios, because when more criteria are used, less and less stocks can meet the criteria, hence the portfolios become more volatile and investors do not enjoy the benefits from diversification.Keywords: Graham; Lynch; Stocks; the Indonesia Stock Exchange (IDX)JEL Classification: G11, G17